THE GALLERY WALK TECHNIQUE (GWT) ON WRITING SKILLS OF ANNOUNCEMENT TEXT - Khairunnisah Khairunnisah; Happy Sri Rezeki Purba (Linguistik : Jurnal Bahasa dan Sastra, 2020)
The research purpose is to improve writing skill on writing announcement text by using Gallery Walk Technique (GWT). It is conducted by using Classroom Action Research as the methodology of the research. The technique of analyzing the data by quantitative and qualitative. The quantitative data apply the tests, wether the qualitative are observation sheet, interview and photography evidence. This research accomplished in three terms, the first is pre-test, then first cycle, the last is second cycle and each cycle consisted of four steps of action research (planning, acting, observing, and reflecting). Pre-test conducted in one meeting, the first cycle conducted in two meetings and the second cycle conducted also in two meetings. In this research, the researcher uses 5 indicators, they are content, organization, vocabulary, grammar, and mechanics. In pre-research, most of the participants are still not able to mastered the indicators. After that, in first cycle there is an improvement on participants’ test. In this cycle, organization and mechanics became indicators that are quite confusing for them. The last, in second cycle 87% of the students have mastered 5 indicators of success mentioned above. As the conclusion, there is an improvement on writing announcement achievement from pre-test, first cycle and second cycle.